2018
DOI: 10.1001/jamainternmed.2018.3981
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mobile Device–Supported Single-Patient Multi-crossover Trials on Treatment of Chronic Musculoskeletal Pain

Abstract: IMPORTANCE Individually designed single-patient multi-crossover (n-of-1) trials can facilitate tailoring of treatments directed at various conditions, including chronic musculoskeletal pain (CMSP) but are potentially burdensome, which may limit uptake in research and practice.OBJECTIVES To determine whether patients randomized to participate in an n-of-1 trial supported by a mobile health (mHealth) app would experience less pain and improved global health, adherence, satisfaction, and shared decision making co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
118
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(118 citation statements)
references
References 40 publications
0
118
0
Order By: Relevance
“…It can capture intraindividual variability in health behaviors over time, aiming to identify individual responses to a given intervention in a controlled trial, which provides a great opportunity to assess the personalization potential of different diets, nutrients, or nutrition supplements ( 16 18 ). The idea of n -of-1 has been applied in special education, psychotherapy, psychology, and pharmaceutical studies for decades to test the individual response to specific drugs or treatments ( 19 23 ). A previous study reported the efficacy of mexiletine on reducing muscle stiffness in patients with nondystrophic myotonia using a series of n -of-1 trials ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…It can capture intraindividual variability in health behaviors over time, aiming to identify individual responses to a given intervention in a controlled trial, which provides a great opportunity to assess the personalization potential of different diets, nutrients, or nutrition supplements ( 16 18 ). The idea of n -of-1 has been applied in special education, psychotherapy, psychology, and pharmaceutical studies for decades to test the individual response to specific drugs or treatments ( 19 23 ). A previous study reported the efficacy of mexiletine on reducing muscle stiffness in patients with nondystrophic myotonia using a series of n -of-1 trials ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…The success of this clinical implementation is dependent on the study design (what is being compared), and the willingness and collaboration of the patient, and the capacity of the clinician to design and implement an n-of-1 trial. With more than 2000 of these trials published to date, examples of previous implementations include an appbased study of the treatment of chronic musculoskeletal pain (Kravitz et al, 2018;Odineal et al, 2019), as well as stimulant effectiveness among people with attention deficit/hyperactivity disorder (Nikles et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It can capture intra-individual variability in health behaviors over time, aiming to identify individual response to a given intervention in a controlled trial, which provides great opportunity to answer the personalization potential of different diets, nutrients or nutrition supplements [16][17][18] . The idea of n-of-1 has been applied in special education, psychotherapy, psychology and pharmaceutical studies for decades to test the individual response to specific drugs or treatments [19][20][21][22][23] . Stunnenberg et al reported the efficacy of mexiletine on reducing muscle stiffness in patients with nondystrophic myotonia (NDM) using a series of nof-1 trials 24 .…”
Section: Introductionmentioning
confidence: 99%